LEGAL POSITION OF RESTORATIVE JUSTICE IN QANUN JINAYAT - Muhammad Ihsan (Syarah: Jurnal Hukum Islam & Ekonomi, 2020)
The penal theory that exists is basicly aimed at achieving justice, therefore the achievement model can be devide into two models, namely the retributive justice model and the restorative justice model. The retributive justice model establish justice based on the philosophy of retaliation, while the restorative justice model is based on the philosophy of recovery. In the case of criminalization in the Criminal Code which is also maintained in the Qanun Jinayat, the philosophy of justice adopted is the first model. Thus, in the convictions of cases of offenders of jinayat offenses, Qanun Jinayat also emphasizes the principle of retributive justice. Meanwhile, the concept of restorative justice in the criminal law system in Indonesia is only applied to cases of children who are dealing with the law and are also adopted by Qanun Jinayat. The concept of restorative justice is basically not known in the Aceh Qanun Jinayat, namely Qanun Number 6 of 2014, but based on the sound of Article 66 of this qanun "If a child who has not reached the age of 18 (eighteen) years commits or is suspected of committing Jarimah, then the child is subject to examination. guided by the laws and regulations regarding juvenile criminal justice ", then automatically every case of children who face the law will be returned to the provisions contained in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System which is familiar with the restorative justice system and diversion. The concept of not being able to provide protection and respect for the interests of victims and perpetrators. This is a conventional mechanism that is based on the enforcement of the criminal justice system without seeing the reality in society, without looking at the interests of the community, and without seeing the benefits. Based on this description, it can be used as an adequate introduction in promoting the concept of restorative justice in the criminal justice system process in Indonesia, especially in Aceh in implementing qanun jinayat which is relevant for its philosophical roots to Islamic criminal law through the concept of diyat. Based on these problems, it is important to study more deeply related to the legal position of restorative justice in the Aceh Jinayat Qanun considering that Aceh applies Islamic law in its regulations